Congresos - Seminario Destinos Turisticos Inteligentes 2017 - Libro De Actas 2017
DOI: 10.14198/destinos-turisticos-inteligentes.2017.02
|View full text |Cite
|
Sign up to set email alerts
|

La relativa importancia de la velocidad en las conexiones WIFI

Abstract: Los turistas quieren acceder a una conexión WiFi desde que llegan a sus destinos, para evitar sobrecargos en sus facturas telefónicas. Entidades públicas y privadas ofrecen este servicio en todo el mundo, pero los turistas suelen quejarse cuando es lento o poco fiable. La velocidad parece ser el factor más importante que determina el nivel de satisfacción de los viajeros con el WiFi, por lo que testamos esta hipótesis centrándonos en los hoteles. Los datos sobre velocidad de conexión son proporcionados por Hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
1
Order By: Relevance
“…By finding a significant link between Wi-Fi speed in hotels and customer satisfaction, the present study contributes to an identified research gap. It advances the Spanish-language study available on the subject (Mellinas, 2017) which did not show a significant correlation between Wi-Fi speed in hotels and customer satisfaction.…”
Section: Theoretical Implicationsmentioning
confidence: 82%
See 3 more Smart Citations
“…By finding a significant link between Wi-Fi speed in hotels and customer satisfaction, the present study contributes to an identified research gap. It advances the Spanish-language study available on the subject (Mellinas, 2017) which did not show a significant correlation between Wi-Fi speed in hotels and customer satisfaction.…”
Section: Theoretical Implicationsmentioning
confidence: 82%
“…This study is based on a widely accepted model, according to which hotel customer satisfaction is determined by the quality of hotel services (Berezina et al, 2015;Mellinas, 2017;Moliner-Vel azquez et al, 2019). The factors used in this study are the four components of the hotel rankings sourced from the www.tripadvisor.com.au website as follows: location, service, cleanliness and value (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…La manera en la que se conecta es mediante conexión wifi asegurándonos de que tanto como el dispositivo móvil y la TV se encuentren conectados a la misma red para que la aplicación pueda detectar la TV, la aplicación la detectara automáticamente el televisor y permitirá al usuario poder manipular las distintas funciones (Mellinas, 2017).…”
Section: Ilustración 6 Lg Televisiónunclassified